2006
DOI: 10.1016/j.cardiores.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute PKCδ inhibition limits ischaemia–reperfusion injury in the aged rat heart: Role of GSK-3β

Abstract: These results provide novel evidence for cardioprotection through acute PKCdelta inhibition in aged rat heart following I/R. Our results also suggest, for the first time, a key role for mitochondrial GSK-3beta as a cellular basis for the protection associated with PKCdelta inhibition with ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
44
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 39 publications
8
44
1
Order By: Relevance
“…6), suggesting that beneficial effects of the peptide are related to biochemical inhibition of this PKCd activation mechanism. Nuclear translocation of PKCd is critical for the initiation of cytotoxic or proapoptotic signaling (Humphries et al, 2008;Pabla et al, 2011), and inhibition of PKCd nuclear translocation was reported to be cytoprotective following ischemia-reperfusion (Kostyak et al, 2006), focal cerebral ischemia (Shimohata et al, 2007), and radiation damage (Wie et al, 2014). Nuclear translocation is required for cleavage of PKCd, which may increase PKCd activity by removal of the regulatory domain (Okhrimenko et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…6), suggesting that beneficial effects of the peptide are related to biochemical inhibition of this PKCd activation mechanism. Nuclear translocation of PKCd is critical for the initiation of cytotoxic or proapoptotic signaling (Humphries et al, 2008;Pabla et al, 2011), and inhibition of PKCd nuclear translocation was reported to be cytoprotective following ischemia-reperfusion (Kostyak et al, 2006), focal cerebral ischemia (Shimohata et al, 2007), and radiation damage (Wie et al, 2014). Nuclear translocation is required for cleavage of PKCd, which may increase PKCd activity by removal of the regulatory domain (Okhrimenko et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al 31 reported that PKC activation induces GSK-3β phosphorylation, and that PKC-δ interacts with GSK-3β in several cell lines. 31,32 in contrast, PKCε might indirectly regulate GSK through phosphatidylinositol-3-kinase (Pi3K), because the induction of a dominantnegative PKCε blocks the activity of Pi3K induced by phorbol ester and insulin. 33 Therefore, the selective PKC isoform responsible for modulating GSK-3β remains an area of interest for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation (or preservation) of phospho-Ser9-GSK-3β level on reperfusion and anti-infarct tolerance have been observed in rat, rabbit or mouse hearts treated with ischemic preconditioning, 51,55-57 ischemic postconditioning, 48,58 bradykinin, 59 opioids, 60,61 EPO, 57,62 an adenosine A1/A2 receptor agonist, 63 an A3 receptor agonist, 64 PKC-ε activator, 65 PKC-δ inhibitor, 66 isoflurane, 67 lipopolysaccharide, 68 sildenafil, 69 xenon 70 or resveratrol. 71 GSK-3β phosphorylation by these apparently unrelated interventions is explained by the fact that GSK-3β is a substrate of multiple pro-survival protein kinases, including Akt, PKC-ε, extracellular signal-regulated kinase (ERK) and protein kinase G, and GSK-3β phosphorylation is therefore a step to which multiple protective signaling pathways converge.…”
Section: Gsk-3β and Tolerance Of Cardiomyocytes To Necrosismentioning
confidence: 99%